PENILAIAN RUMAH SEHAT DAERAH PESISIR KAMPUNG BAHARI KOTA BENGKULU - Allensha Mezza reriscie; Nopia Wati; Julia finola Ifanasari; Parwito Parwito (Gayaku Publisher, 2025)
The aim of this research is to determine the description of the condition of houses and the assessment of healthy houses in Kampung Bahari, Bengkulu City. The method used in observation activities is to use direct observation techniques and interviews with respondents using a cross-sectional approach which is defined as a description or description of community health. and factors that influence the health of an area both qualitatively and quantitatively. The subjects of this research were 95 families.The conclusion of this research is that from the results of a review or direct observation that was carried out in the coastal area of RT 12 Kampung Bahari, Bengkulu City, with 20 heads of families who had been assessed, the total of the houses inspected were declared healthy houses with the score of each resident's house reaching The value of the criteria for a healthy home is >660. Apart from that, problems are still found in the assessment of healthy houses in the Bengkulu city area, namely the lighting in the house is still not bright enough, so it is not clear enough to be used for normal reading with a percentage of 45%, people's behavior is never to open the family room window with a percentage of 50%. , then the behavior of cleaning the yard which is sometimes carried out with a percentage of 50%, the behavior of throwing away baby and toddler feces which are thrown into rivers/gardens/pools/randomly with a percentage of 50%, apart from that the problem of waste disposal facilities already existing, watertight , but not covered with a percentage of 100%.